2006
DOI: 10.1002/ijc.22494
|View full text |Cite
|
Sign up to set email alerts
|

Lack of BK virus DNA sequences in most transitional‐cell carcinomas of the bladder

Abstract: BK virus (BKV), a common human polyomavirus infection latent in the kidneys, can reactivate with immunosuppression to cause renal disease. Some have suggested that BKV may contribute to the development of bladder cancer, and BKV sequences have been reported from bladder tumors. To further examine the role of BKV in human bladder cancer, a series of bladder tumors was investigated for BKV genomic sequences. Fresh‐frozen specimens from 76 transitional cell carcinoma tissues and 46 paired adjacent normal urotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 25 publications
2
41
1
Order By: Relevance
“…In a case -control study, Newton et al (2005) found no association between prevalence or titres of anti-BKV antibodies and diagnosis of bladder cancer. A recent tissue-based study detected BKV DNA by PCR in only 5.5% of urothelial carcinomas, all of which were negative on IH for BKV T-Ag (Rollison et al, 2007). Similarly, we found no evidence of PV T-Ag in urothelial carcinoma from 20 immunocompetent patients.…”
Section: Discussionsupporting
confidence: 49%
“…In a case -control study, Newton et al (2005) found no association between prevalence or titres of anti-BKV antibodies and diagnosis of bladder cancer. A recent tissue-based study detected BKV DNA by PCR in only 5.5% of urothelial carcinomas, all of which were negative on IH for BKV T-Ag (Rollison et al, 2007). Similarly, we found no evidence of PV T-Ag in urothelial carcinoma from 20 immunocompetent patients.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, a statistically significant association between urine cytological evidence of PyV infection (decoy cells) and BC was also demonstrated in immunocompetent patients (18). Despite this experimental and epidemiological evidence, clinical cases of PyV-associated urological malignancies are rare and presented mainly as isolated case reports, mostly in transplant recipients or rarely in immunocompetent patients (17,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…78 Rollison et al concluded that BKV did not play a major role in the pathogenesis of bladder carcinoma, as only 5.5% of bladder samples were positive for the presence of the BKV genome and none of them showed T Ag expression. 80 In a case report, a single patient who developed PVAN and a subsequent carcinoma of the bladder that was diffusely positive for BKV T Ag expression was described. 81 The involvement of BKV in kidney cancer is not well established.…”
mentioning
confidence: 99%
“…[82][83][84] The presence of BKV sequences in kidney cancer samples also seems to vary among different cohorts of patients. 50,51,[74][75][76][77][78][79][80][81][82][83][84] Kausman et al reported the case of a 10-year-old child with a carcinoma of the donor renal pelvis following BKV allograft nephropathy. Removal of the primary tumor and cessation of immunosuppression led to regression of the secondary tumors and a return to health.…”
mentioning
confidence: 99%